2012
DOI: 10.3892/ijo.2012.1733
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 promotes tumor progression and confers malignancy phenotypes of colon cancer by regulating the focal adhesion kinase pathway and adhesion molecules

Abstract: Abstract. Studies suggest a tumor-promoting function of sphingosine kinase 1 (SphK1) in some types of human tumors, however, its effect on colon cancer is still unclear. The aims of this study were to investigate the roles of SphK1 in the progression and tumor cell phenotypic changes in colon cancer. Moreover, the focal adhesion kinase (FAK) pathway and the expression of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) were detected to explore the mechanisms of SphK1 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 33 publications
(33 reference statements)
1
36
0
Order By: Relevance
“…For example, SPHK1 promotes the metastasis of esophageal cancer by activating the EGFR (epidermal growth factor receptor) pathway 22 and confers malignant phenotypes in colon cancer by regulating the PTK2/FAK (protein tyrosine kinase 2) pathway 23 . EGFR activation leads to the EMT, 24 and PTK2 is necessary for the process of TGFB/TGFβ (transforming growth factor β)-induced EMT 25 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, SPHK1 promotes the metastasis of esophageal cancer by activating the EGFR (epidermal growth factor receptor) pathway 22 and confers malignant phenotypes in colon cancer by regulating the PTK2/FAK (protein tyrosine kinase 2) pathway 23 . EGFR activation leads to the EMT, 24 and PTK2 is necessary for the process of TGFB/TGFβ (transforming growth factor β)-induced EMT 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis can be triggered by two signaling pathways, the extrinsic pathway (death receptor pathway) and the intrinsic pathway (the mitochondrial pathway) [12]. Poly(ADP-ribose) polymerase (PARP) is a key signaling nuclear protein involved in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that SPHK1 protein expression is unregulated in various types of cancer, including prostate cancer (13), gastric cancer (14), glioblastoma multiforme (15), intestinal adenoma (16), acute erythroleukemia (17), colon cancer (18), salivary gland carcinoma (19) and glioma (20). In addition, there is plenty of evidence indicating that activation of SPHK1 is associated with anti-apoptosis effects, and the transformation, proliferation and survival of tumor cells (21,22).…”
Section: Introductionmentioning
confidence: 99%